Around the Logicity of Implication - Banda Marroquín, Obdulio (Pensamiento. Revista de Investigación e Información Filosófica, 2020)
The assignment of truth values assigned bivalent logic to conditional in tabular standard definition, is based on epistemological nature categories, which are incompatible with the formal and abstract nature of logical structures. The logic is intended to qualify with epistemological categories, non-epistemological formal structures. This assignment evades the rigor of logicality that demand any formal structure and therefore it lacks rational necessity.